Interactome Profiling of N-Terminus-Truncated NS1 Protein of Influenza A Virus Reveals Role of 14-3-3γ in Virus Replication - Kuo, Rei-Lin; Tam, Ee-Hong; Woung, Chian-Huey; Hung, Chu-Mi; Liu, Hao-Ping; Liu, Helene Minyi; Wu, Chih-Ching (Pathogens (Basel), 2022)
Influenza A virus is transmitted through a respiratory route and has caused several pandemics throughout history. The NS1 protein of influenza A virus, which consists of an N-terminal RNA-binding domain and a C-terminal effector domain, is considered one of the critical virulence factors during influenza A virus infection because the viral protein can downregulate the antiviral response of the host cell and facilitate viral replication. Our previous study identified an N-terminus-truncated NS1 protein that covers the C-terminus effector domain. To comprehensively explore the role of the truncated NS1 in cells, we conducted immunoprecipitation coupled with LC-MS/MS to identify its interacting cellular proteins. There were 46 cellular proteins identified as the components of the truncated NS1 protein complex. As for our previous results for the identification of the full-length NS1-interacting host proteins, we discovered that the truncated NS1 protein interacts with the γ isoform of the 14-3-3 protein family. In addition, we found that the knockdown of 14-3-3γ in host cells reduced the replication of the influenza A/PR8 wild-type virus but not that of the PR8-NS1/1-98 mutant virus, which lacks most of the effector domain of NS1. This research highlights the role of 14-3-3γ, which interacts with the effector domain of NS1 protein, in influenza A viral replication.